Golabz-based interactive learning design about simple harmonic motion on pendulum swing - Erwin Hartaman Gea; Alvama Pattiserlihun; Debora Natalia Sudjito (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
Physics learning about simple harmonic motion on a pendulum swing is interesting to be deeply learned because there are various physical quantities, practicum, formula derivation, and representation. In online learning, inquiry physics learning that provides independent practicum, online access, systematics, and interactive is needed. This research aims to design Golabz-based interactive learning and investigate its effect on students' understanding of simple harmonic motion on a pendulum swing. This research uses the RD methods of the ADDIE type. The respondents were 7 second-year undergraduate students of the Department of Physics Education, UKSW, randomly chosen. The research instruments used are a validation sheet of material and media experts, an observation sheet, an evaluation sheet, and a questionnaire. All data gathered are analyzed using the qualitative descriptive technique. The result showed that the material and media met the eligibility criteria of 70,66% and 78,66%; all respondents can do 88,8% learning on average; all respondents can give positive responses of 89,79% on average in the questionnaire; and all respondents get evaluation score of 91,84% in average. Thus, Golabz-based interactive learning design is adequate to help students understand simple harmonic motion on a pendulum swing and can be one of the alternative online learning that presents interactive inquiry learning.